MEKANISME DALAM PELAKSANAAN AKSESIBILITAS PENYANDANG DISABILITAS - RINDA PHILONA; NOVITA LISTYANINGRUM; DEWI ASMAWARDHANI; BAIQ NURAINI DWI S.; BAIHAQI SYAKBANI (GANEC SWARA, 2023)
In Law Article 41 Paragraph (2) Law no. 9 of 1999 concerning Human Rights it is written that: "Every person with disabilities, the elderly, pregnant women and children, has the right to receive special facilities and treatment. The government itself often does not care about education, the environment and the conditions of people with disabilities. The aim of this research is to find out and understand the mechanisms for implementing accessibility for people with disabilities. By using the Legislative Regulations, conceptual approach. In constructing buildings and public facilities, what is usually considered is whether they are in accordance with the Terms of Reference which are the reference for the Public Works Department to construct. Meanwhile for the rehabilitation or development process, initially a proposal is made by the relevant agency, then the proposal is submitted to the House of Representatives, then after receiving the disposition of the DPR, then the Public Works Service will carry out its work function. Meanwhile, the work reference for the Public Works Service is not based on the Regulation of the Minister of Public Works concerning Technical Guidelines for Facilities and Accessibility in Buildings and the Environment, in which the regulation states the mechanism for the construction and rehabilitation of facilities